The long-term earnings consequences of general vs. specific training of the unemployed - Anders Stenberg; Olle Westerlund (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
Training programs for the unemployed typically involve teaching a specific skill to ease the transition into employment. However, in 1997, the Swedish unemployed could choose general/theoretical training through enrollment in one year of full-time studies at the upper secondary school level. This study provides an empirical assessment of the relative earnings impact of general vs. specific training 13 years post-enrollment. In the long term, general training may compensate for the short-term relative earnings loss by enhancing the ability to adapt to changes in demand for skills. The analyses are based on population register data 1990-2010 and an unusually rich set of control variables. The results indicate that both programs are associated with earnings increases. Our relative program estimates reveal a short-term advantage of specific training that converges within 5-7 years. With a longer perspective, there is considerable heterogeneity in the relative earnings estimates. For females with short educations, the earnings increases following general training substantially exceed those following specific training.
Keywords: I21; J62; J68; 330; active labor market programs; adult education; vocational training; general training